Characterizing the degradation of alginate hydrogel for use in multilumen scaffolds for spinal cord repair. Issue 3 (12th November 2015) - Shahriari, Dena; Koffler, Jacob; Lynam, Daniel A.; Tuszynski, Mark H.; Sakamoto, Jeffrey S.
Abstract: Alginate was studied as a degradable nerve guidance scaffold material in vitro and in vivo . In vitro degradation rates were determined using rheology to measure the change in shear modulus vs time. The shear modulus decreased from 155 kPa to 5 kPa within 2 days; however, alginate samples maintained their superficial geometry for over 28 days. The degradation behavior was supported by materials characterization data showing alginate consisted of high internal surface area (400 m 2 /g), which likely facilitated the release of cross‐linking cations resulting in the rapid decrease in shear modulus. To assess the degradation rate in vivo, multilumen scaffolds were fabricated using a fiber templating technique. The scaffolds were implanted in a 2‐mm‐long T3 full transection rodent spinal cord lesion model for 14 days. Although there was some evidence of axon guidance, in general, alginate scaffolds degraded before axons could grow over the 2‐mm‐long lesion. Enabling alginate‐based scaffolds for nerve repair will likely require approaches to slow its degradation. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 611–619, 2016.